Kinanthropometric attributes of young male combat sports athletes - Catikkas, S.; Kurt, C.; Atalag, O. (Collegium Antropologicum, 2013)
Although there are enough studies concerning the kinanthropometric attributes of players of sports such as football, basketball, or volleyball in Turkey, there are not enough studies on the same for combat sports. Hence, our aim is to assess the kinanthropometric attributes of different combat sports like karate, taekwondo, judo and kickboxing. The present study included 48 national level male athletes from four different combat sports (age, 20.3 (3.19) years; number of years playing the sport, 8.33 (4.59); height, 174.3 (7.15) cm; weight, 67.35 (10.55 kg). Skinfold thickness was measured with a skinfold caliper (Holtain Ltd., UK), and Yuhazs formula was used to calculate the body fat percentage. Somatotype assessment was carried out with a computer program (Sweat Technology Trial Version, South Australia). Width measurements were obtained with a slide caliper (HLT-100, Holtain Ltd.), and girth measurements were obtained with a non-flexible tape measure. The data obtained were analyzed with the computer program SPSS 17.0 in terms of the SD. The findings were as follows: body mass index (BMI), 22.00 (2.66) kg/m2; body fat percentage, 12.20% (3.07%); endomorphic component, 2.9 (1.30); mesomorphic component, 4.25 (1.30); and ectomorphic component, 3.10 (1.30). The cormic index was 51.99% (1.88%); Monourier index, 92.39% (4.47%); Acromio-iliac index, 60.87% (6.61%); Martine index, 6.29% (0.70%); Biacromial index, 22.58% (0.99%); and hip index, 13.91% (0.86%). The mesomorphic component was found to be dominant in our study. Although BMI were found to be normal, body fat percentages were low. According to body proportions, the athletes who participated in this study had wide shoulders, narrow hips, and medium-sized trunks.